2017
DOI: 10.1590/0037-8682-0451-2016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant therapy in experimental Chagas disease

Abstract: Introduction: Stimulation of inflammatory mediators such as cytokines and chemokines may cause oxidative stress in Chagas disease. In this study, we evaluated the merit of vitamins C and E as antioxidant therapy to minimize the oxidative stress-induced damage in an experimental model of Chagas disease. Methods: Ninety-six Swiss mice were infected with Trypanosoma cruzi QM2 and treated with vitamins C, E, or both (C/E) for 60 and 120 days, and their effects compared to placebo administration were evaluated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In contrast, treatment with vitE only had a prooxidant effect evidenced by an increase in lipid peroxidation in the skeletal muscle of acutely infected mice and no antioxidant effect in chronic Chagas mice. In another study, Novaes et al [48] used a similar vitE dose as reported by Tieghi et al [53] and showed reduction in lipid peroxidation in the cardiac muscle of vitE-treated infected mice, though these authors also noted no increase in the antioxidant enzyme activities. Others showed that vitC had a prooxidant effect 3 Oxidative Medicine and Cellular Longevity Heart, heart mitochondria Cv: carvedilol; SOD: superoxide dismutase; CAT: catalase; MDA: malondialdehyde; GSH: glutathione; GST: glutathione S-transferase; FRAP: plasma antioxidant capacity; TBARS: thiobarbituric acid reactive substances; PCN: protein carbonyl levels; PBN: phenyl-alfa-tert-butyl nitrone; B100: 100 mg/kg of body weight benznidazole; B50: 50 mg/kg benznidazole; C100: 100 mg/kg curcumin; dpi: days postinfection.…”
Section: Antioxidant Effects In Experimental Models Of Chagas Diseasementioning
confidence: 89%
See 2 more Smart Citations
“…In contrast, treatment with vitE only had a prooxidant effect evidenced by an increase in lipid peroxidation in the skeletal muscle of acutely infected mice and no antioxidant effect in chronic Chagas mice. In another study, Novaes et al [48] used a similar vitE dose as reported by Tieghi et al [53] and showed reduction in lipid peroxidation in the cardiac muscle of vitE-treated infected mice, though these authors also noted no increase in the antioxidant enzyme activities. Others showed that vitC had a prooxidant effect 3 Oxidative Medicine and Cellular Longevity Heart, heart mitochondria Cv: carvedilol; SOD: superoxide dismutase; CAT: catalase; MDA: malondialdehyde; GSH: glutathione; GST: glutathione S-transferase; FRAP: plasma antioxidant capacity; TBARS: thiobarbituric acid reactive substances; PCN: protein carbonyl levels; PBN: phenyl-alfa-tert-butyl nitrone; B100: 100 mg/kg of body weight benznidazole; B50: 50 mg/kg benznidazole; C100: 100 mg/kg curcumin; dpi: days postinfection.…”
Section: Antioxidant Effects In Experimental Models Of Chagas Diseasementioning
confidence: 89%
“…The number of parasites used for challenge infection was variable, ranging from 1 × 10 1 to 1 × 10 5 blood trypomastigotes, that was mostly related to virulence of the parasite isolates but unrelated to the development of the acute or chronic phase. The antioxidant compounds used in these studies included phenyl-α-tert-butyl nitrone (PBN) [50,51], carvedilol, vitamin E (vitE) and/or vitamin C (vitC) [52,53], melatonin [54], curcumin [55], resveratrol, and astaxanthin [56]. Vitamin C was the most commonly used antioxidant, evalu-ated in five of the published studies.…”
Section: Antioxidant Effects In Experimental Models Of Chagas Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin C/E treated group showed a reduction of TBARS. The antioxidant action of vitamins C and E reduced oxidative stress in the acute and chronic phases of Chagas disease with a marked effect following co-administration, indicating inherent synergism (Tieghi et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike acute infections, chronic Chagas disease is often associated with the downregulation of antioxidant enzymes. This process seems to be related to the enzymatic exhaustion created by sustained oxidative stress, which is closely related to the severity of chronic Chagas cardiomyopathy [ 26 , 67 ].…”
Section: Discussionmentioning
confidence: 99%